2017
DOI: 10.1590/abd1806-4841.20175377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characteristics, staging, and outcomes of individuals with AIDS-associated Kaposi's sarcoma at an university hospital

Abstract: BackgroundKaposi's sarcoma continues to be the most common human immunodeficiency virus - associated neoplasm with considerable morbidity and mortality.ObjectiveTo describe the clinical and laboratory characteristics, initial staging, and outcomes of aids patients with Kaposi's sarcoma at an university hospital of Recife, Pernambuco.MethodsThis is a descriptive study with analytic character, retrospective, of a case series between 2004 and 2014.ResultsOf the 22 patients included in the study, 20 were aged <40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Similar to what we found, recent studies from low- and middle-income countries (LMICs) suggest that, despite significant expansion of HIV programs in these regions, KS may remain an important cause of morbidity and mortality among patients newly enrolling for HIV care [ 27 29 ]. A recent multinational study across Latin American countries reported that the risk for KS was 41% lower in 2005 compared to 2010 (adjusted HR 0.59, 95% CI 0.40–0.87), and 70% higher in 2012 (adjusted HR 1.70, 95% CI 1.37–2.09) [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similar to what we found, recent studies from low- and middle-income countries (LMICs) suggest that, despite significant expansion of HIV programs in these regions, KS may remain an important cause of morbidity and mortality among patients newly enrolling for HIV care [ 27 29 ]. A recent multinational study across Latin American countries reported that the risk for KS was 41% lower in 2005 compared to 2010 (adjusted HR 0.59, 95% CI 0.40–0.87), and 70% higher in 2012 (adjusted HR 1.70, 95% CI 1.37–2.09) [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, after the antiretroviral therapy (ART) was widely used from 1996, the KS incidence dropped dramatically [11,12]. KS can cause skin lesions of purple, red, or brown spots, most often on the legs or face, but they can also develop in other parts of the body [13,14]. These skin lesions are very prominent and may attract attention from colleagues or passersby, which is a huge social and psychological burden for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Four types of KS are described: classic (sporadic or Mediterranean), endemic (African), epidemic (or HIV-related), and iatrogenic (induced by immunosuppressive drugs) [1][2][3][4]. It mostly involves the skin (especially in distal limbs), but the KS extension to deeper structures such as bone and joints can be destructive and lead to severe functional impairment [5].…”
Section: Introductionmentioning
confidence: 99%